RISE OF INDIAN DEFENSE INDUSTRY - zafar, javed (TRANSBORDERS: International Relations Journal, 2025)
India, the world's most populous country, possesses the second-largest military and the fourth-largest defense budget globally. Historically, India has been one of the largest arms importers. However, over the past two decades, the country has made significant efforts to reduce its dependence on imports and achieve self-reliance in defense manufacturing. To accomplish this goal, India has introduced major policy reforms, including opening up the defense sector to private companies and launching extensive indigenization initiatives. These measures aim to strengthen domestic defense production and position India as a key player in the global defense industry. This paper analyzes the historical trajectory of India's defense imports, examining the factors that contributed to its reliance on foreign weaponry. It also explores India's strategic efforts to reduce imports by promoting indigenous manufacturing and fostering technological advancements. Furthermore, the paper highlights India's emergence as a key defense exporter on the global stage, assessing its growing influence in international arms trade.